Developments in American Politics 8
XX, 323 p. 23 illus.
Keywords: Written by a team of leading experts of American politics, this text provides an authoritative and informed analysis of the latest issues, trends and developments. Fully up-to-date, the book takes full account of the political landscape that followed the 2016 elections and the controversies which face Trump’s administration.